2016
DOI: 10.1016/j.jsb.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Easy mammalian expression and crystallography of maltose-binding protein-fused human proteins

Abstract: We present a strategy to obtain milligrams of highly post-translationally modified eukaryotic proteins, transiently expressed in mammalian cells as rigid or cleavable fusions with a mammalianized version of bacterial maltose-binding protein (mMBP). This variant was engineered to combine mutations that enhance MBP solubility and affinity purification, as well as provide crystal-packing interactions for increased crystallizability. Using this cell type-independent approach, we could increase the expression of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…The resulting PCR products, isolated after digestion with Not I and Xho I were subcloned in frame with the mMBP gene of pHLmMBP-115, a mammalian expression vector derived frompHLsec42. Restrictions enzymes were purchased from Fermentas (San Leon-Rot, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting PCR products, isolated after digestion with Not I and Xho I were subcloned in frame with the mMBP gene of pHLmMBP-115, a mammalian expression vector derived frompHLsec42. Restrictions enzymes were purchased from Fermentas (San Leon-Rot, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For analyzing the oligomerization state of egg coat protein precursors, medaka ZI-1,2 (which does not contain N-glycosylation sites) was expressed in HEK293T cells (DuBridge et al, 1987) , grown in DMEM medium supplemented with 4 mM L-Gln 2% fetal bovine serum and transiently transfected using 25 kDa branched PEI (Aricescu et al, 2006;Bokhove et al, 2016b) . GnTI-deficient HEK293S cells (Reeves et al, 2002) were used to express ZI-3 carrying Endoglycosidase H (Endo H)-sensitive Man5GlcNAc2 N-glycans.…”
Section: Recombinant Protein Expression and Purificationmentioning
confidence: 99%
“…GnTI-deficient HEK293S cells (Reeves et al, 2002) were used to express ZI-3 carrying Endoglycosidase H (Endo H)-sensitive Man5GlcNAc2 N-glycans. These carbohydrate chains were then enzymatically trimmed to single GlcNAc residues during protein purification, which was performed by batch immobilized metal ion affinity (IMAC) using nickel agarose slurry (Ni-NTA, QIAGEN or Ni Sepharose High Performance, GE Healthcare) and size-exclusion chromatography (SEC) using a Superdex 200 Increase 10/300 GL column (GE Healthcare) equilibrated against 20 mM HEPES pH 7.5, 150 mM NaCl (Bokhove et al, 2016b) .…”
Section: Recombinant Protein Expression and Purificationmentioning
confidence: 99%
“…One approach to stabilize flexible proteins has been described by Moon and coworkers and utilizes maltosebinding protein (MBP) with surface-entropy reduction (SER) mutations as an N-terminal carrier protein to enhance protein crystallization (Moon et al, 2010). MBP has been reported to enhance the solubility of proteins when expressed as an N-terminal fusion in Escherichia coli (Waugh, 2016;Jin et al, 2017) and mammalian expression systems (Reuten et al, 2016;Bokhove et al, 2016), but to date this has not been reported for insect-cell expression systems. We describe the expression of the FXIIa protease domain as a secreted MBP fusion using DES, which facilitated the crystal structure determination of MBP-FXIIa His in the active conformation in complex with the peptidomimetic inhibitor d-Phe-Pro-Arg chloromethyl ketone (PPACK).…”
Section: Introductionmentioning
confidence: 99%